A Multiwavelength Study of the Dynamic Environment Surrounding the Fuor v960 Mon - Perez-Marquez, S; Weber, P (Institute of Physics, 2025)
The evolution of young stars and planet-forming environments is intrinsically linked to their nascent surroundings. This is particularly evident for FU Orionis (FUor) objects—a class of young protostars known for dramatic outbursts resulting in significant increases in brightness. We present a case study of V960 Mon, an FUor that has recently been found to show signs of a fragmenting spiral arm, potentially connected to planet formation. Our study explores the large-scale environment (103-104 au) and incorporates Atacama Large Millimeter/submillimeter Array band 3, band 4, and band 6 continuum data, molecular emissions from 12CO, 13CO, C18O, SiO, DCO+, N2D+, and DCN, alongside optical and near-infrared observations from Very Large Telescope (VLT) Multi Unit Spectroscopic Explorer (MUSE) and VLT Spectro-Polarimetric High-contrast Exoplanet REsearch instrument (SPHERE). We map a region of 20″ across where we find tantalizing emissions that provide a unique view of a young group of protostars, including the discovery of a class-0 protostar to the east of the FUor. The 12CO and SiO tracers suggest that this object is at the base of an outflow, potentially impacting the surrounding medium. The MUSE and SPHERE observations indicate the presence of an elongated feature towards a prominent source to the southeast that may represent interaction between V960 Mon and its surroundings. Moreover, the C18O emission overlaps with the clumps of the detected fragmenting spiral arm. These findings provide the strongest evidence to date for a connection between infalling material, fragmentation, and the intensity outburst of a protostar. Our case study highlights the complex interactions between young stars and their surroundings that drive the evolution of the planet forming environment. © 2025. The Author(s). Published by the American Astronomical Society.